Windmaker. Volume two - Okupe, Roye (Dark Horse Books, 2023)
The Republic of Atala's president has turned into a ruthless despot, and one of his trusted head of secutiry, Director Bo, is forced to choose a side in a civil war that threatens to destroy their beloved nation. The spirit of the WindMaker--an ancient and powerful protector of the Atalians--also begins to awaken within Bo. Is this awakening a ray of hope that will pave a path to salvation, or is this an omen signaling the end of a once prosperous country?